Manhaj Khash Tafsir An-Nur Karya Hasby Ash-Shiddieqy - Asep Fuad; Masykur Masykur (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the manhaj al-Khash Tafsir al-Qur'an an-Nur by scholars of commentators and hadith experts including an Indonesian Muslim scholar who received his Doctoral degree Hanouris Causa (HC) from the Islamic University of Bandung on March 22, 1975 AD. He is Hasby as-Siddieqy, a native of Aceh, where the discussion is more directed to see how Hasby as-Siddieqy realizes the direction of interpretation and explains basics of thought, ideas, ideas and so on. The method used in this research is descriptive and library (library research). The substance of his research is more about theoretical matters, ideas and others. Based on the results of the study, it is known that the Tafsir al-Qur'an an-Nur by Hasby as-Siddieqy, totaling 10 volumes, is expected to answer the challenges of the times that are more practical, systematic, dynamic and very easy to understand by all circles of society. The presence of Tafsir al-Qur'an an-Nur by Hasby as-Siddieqy in various approaches is in line with the realization of government programs to meet the need for the availability of books of interpretation of the Qur'an for the Indonesian people.